The impact of investor recognition on stock returns in Singapore exchange market. - Xu, Yawen. (2013)
This paper aims to explore the effectiveness of investor recognition in explaining the variations in stock returns. It also compares the explanation power of investor recognition with that of earnings and cash flows which are widely accepted as not very effective in justifying stock return fluctuations. Consistent with [Merton, 1987] analysis, we prove that (i) contemporaneous stock returns have a positive correlation with change in investor recognition. (ii) future stock returns are negatively related to changes in investor recognition. (iii) the above relations are stronger for stocks with higher level of idiosyncratic risk. In conclusion, our research indicates that investor recognition should be one of the critical factors to investors and managers in firm valuation.